The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00436-009-1646-z
|View full text |Cite
|
Sign up to set email alerts
|

Prime-boost and recombinant protein vaccination strategies using Sm-p80 protects against Schistosoma mansoni infection in the mouse model to levels previously attainable only by the irradiated cercarial vaccine

Abstract: Advent of an effective schistosome vaccine would contribute significantly toward reducing the disease spectrum and transmission of schistosomiasis. We have targeted a functionally important antigen, Sm-p80, as a vaccine candidate because of its consistent immunogenicity, protective and antifecundity potentials, and important role in the immune evasion process. In this study, we report that using two vaccination approaches (prime boost and recombinant protein), Sm-p80-based vaccine formulation(s) confer up to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
2
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(105 citation statements)
references
References 45 publications
(73 reference statements)
3
98
2
1
Order By: Relevance
“…In vitro experimentation using sera obtained from both mice 17 and baboons 21 that received Sm-p80 vaccine showed killing of schistosomula in the presence of complement. The extent of larval killing was reduced when sera were heat inactivated or CVF was introduced in the incubation media.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In vitro experimentation using sera obtained from both mice 17 and baboons 21 that received Sm-p80 vaccine showed killing of schistosomula in the presence of complement. The extent of larval killing was reduced when sera were heat inactivated or CVF was introduced in the incubation media.…”
Section: Discussionmentioning
confidence: 98%
“…1). The antibodies to Sm-p80, generated in mouse and baboons, following vaccination with a Sm-p80-based vaccine formulation, 17,21 were able to kill schistosomula in vitro in the presence of exogenous complement. The complement-mediated killing effect on schistosomula was partially reversed when CVF was used; this effect was more pronounced when used with the mouse sera but not as remarkable with the baboon sera ( Fig.…”
Section: Role Of Complement In Killing Of Schistosomula In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…At present, to our knowledge, Sm-p80 is the sole schistosome vaccine candidate that has been tested for its prophylactic, antifecundity and therapeutic efficacy in different vaccine formulations and approaches (e.g., naked DNA alone; recombinant protein with adjuvants; and prime with DNA, followed by boosting with protein plus adjuvants) in two experimental animal models (mouse and baboon) of infection and disease. 16,[50][51][52][53][54][55][56][57][58][59][60][61][62] Furthermore, the validity of Sm-p80 as a viable vaccine candidate has been reinforced by the work of five "research groups" who have independently demonstrated reproducible and consistent protective efficacy in mice following challenge infection using calpain or its peptides as an antigen (Nagoya City University Medical School, Nagoya, Japan; 63 [50][51][52][53][54][55][56][57][58][59][60][61][62] ). Sm-p80-based vaccine formulations have three protective effects: worm reduction, antifecundity effect and protection against acute schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…The promising pre-clinical data in combination with the successful scale-up expression of the antigen suggest that Sm-TSP-2 is ready for Phase I trials 25 .The S. mansoni calpain large subunit, Sm-p80, another vaccine candidate is generating promising results in pre-clinical studies. Worm burden and hepatic egg burden were reduced by 70% and 75%, respectively, in mice immunized with a formulation of recombinant Sm-p80 and CpG dinucleotides compared to controls26 . The promising results observed in the mouse model, prompted the group to continue their experiments in a nonhuman primate model; the baboon.Experimentally immunized baboons had a 58% decrease in worm burden compared to the controls27 .…”
mentioning
confidence: 99%